2022
DOI: 10.1091/mbc.e18-10-0682_corr
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the roles of phosphatidylinositol-4,5-bisphosphate and individual subunits in assembly, localization, and function of Saccharomyces cerevisiae target of rapamycin complex 2

Abstract: ARM, a structural motif (3-helix bundle) first described in Armadillo (Drosophila -catenin).BFP, Aequorea victoria green fluorescent protein variant carrying Y66H Y145F substitutions.CaaX box, consensus motif for protein prenylation. eGFP, Aequorea victoria green fluorescent protein variant carrying F64L S65T substitutions. EM-CCD, electron-multiplying charge-coupled device. FITC, fluoroscein isothiocyanate. 5-FOA, 5-fluoro-orotic acid. GFP, Aequorea victoria green fluorescent protein.HEAT repeat, a structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 88 publications
0
1
0
Order By: Relevance
“…This treatment induces PIP 2 phase separation into invaginated domains that cause TORC2 inactivation [ 49 ]. Indeed, it has been shown that PIP 2 depletion reduces TORC2 activity [ 50 ]. All these observations support the idea that neomycin is interfering with PIP 2 availability and PM organization, impairing TORC2 activity and consequently TORC2-dependent Ypk1 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment induces PIP 2 phase separation into invaginated domains that cause TORC2 inactivation [ 49 ]. Indeed, it has been shown that PIP 2 depletion reduces TORC2 activity [ 50 ]. All these observations support the idea that neomycin is interfering with PIP 2 availability and PM organization, impairing TORC2 activity and consequently TORC2-dependent Ypk1 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that PM recruitment of Avo3 requires five or so of its more N-terminal ARM repeats (residues 496-710), which are rich in basic residues (Martinez Marshall et al 2019), suggesting that this segment of Avo3 is solvent-exposed and not closely associated with the rest of TORC2. In addition, our results indicate that docking of Avo3 on the PM is likely the initial step for de novo assembly of TORC2; once there, Avo3 attracts and tethers Tor2-Lst8 couples to the PM, which, after their dimerization, provide a scaffold to recruit the other subunits of TORC2 (Martinez Marshall et al 2019). Hence, Avo3 is essential because it has critical roles in the localization, assembly, and stability of TORC2.…”
Section: Avo3/tsc11mentioning
confidence: 91%
“…It is not clear what evolutionary forces drove organisms in the fungal clade to compose TORC1 and TORC2 using two paralogous TOR proteins (Heitman et al 1991a, Shertz et al 2010, Ikai et al 2011, whereas metazoans constitute mTORC1 and mTORC2 from a single mTOR protein (Saxton & Sabatini 2017). In any event, among the distinctions between Tor1 and Tor2 observed in yeast cells early on (Kunz et al 2000, Sturgill et al 2008) and amply confirmed subsequently (Berchtold & Walther 2009, Nicastro et al 2017, Martinez Marshall et al 2019) is that Tor2 (and TORC2) is located at the plasma membrane (PM) and on endosomes, whereas Tor1 (and TORC1) is found in the cytosol and associated with the cytosolic surface of the vacuole (Figure 2). A similar distribution is observed in mammalian cells for mTORC1 (Sancak et al 2010) and mTORC2 (Ebner et al 2017).…”
Section: A Division Of Labormentioning
confidence: 99%
See 2 more Smart Citations